HUBUNGAN MEKANISME GOOD CORPORATE GOVERNANCE, LEVERAGE DAN UKURAN PERUSAHAAN DENGAN KONSERVATISME AKUNTANSI - Halimatus Sholikhah; Maslichah Maslichah; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This research has aimed to analyze the influence of mechanism of good corporate governance, leverage and company size on accounting conservatism. The population in this study are manufacturing companies registered on the Stock Exchange in 2016-2018. This research used 57 companies that have been selected through a purposive sampling method for three year. The analytical model used in this study was multiple linear regression. The results of this study indicate simultaneously the independent commissioner variable, shareholding by affiliated commissioners, leverage and firm size significantly influence accounting conservatism. Partially independent commissioners, share ownership by affiliated commissioners and company size partially influential. While the size of the company has no effect on accounting conservatism.Keywords : accounting conservatism, mechanism of good corporate governance, leverage and company size